Intelligent power networks of electrical power systems - Kyrylenko, Oleksandr (Publishing House of Lviv Polytechnic National University, 2011)
Problems associated with the development of today’s electrical power engineering are considered. Analysis of the concept “Smart Grid” and peculiarities of its development is made. Basic technological and technical components of the concept implementation have been identified. The problem of identification of the most acceptable decisions for Smart Grid platform realization in Ukraine with regard to those groundworks that found their implementation in power networks has been investigated. Розглянуті проблеми, що пов’язані з розвитком електроенергетики в сучасних умовах. Проведено аналіз концепції Smart Grid та особливостей її розвитку. Визначені основні технологічні та технічні складові реалізації цієї концепції. Досліджена проблема визначення найбільш прийнятних рішень для реалізації платформи Smart Grid в Україні з урахуванням тих напрацювань, що знайшли впровадження в електричних мережах.
Інтелектуальні електричні мережі електроенергетичних систем
Keywords: intelligent power networks; electrical power systems; Smart Grid concept